2014
DOI: 10.2174/092986732134141015161539
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Atherosclerosis: Mechanisms of Disease and New Therapeutic Approaches

Abstract: It has been clear that at least 1 billion adults worldwide are smokers and at least 700 million children are passive smokers at home. Smoking exerts a detrimental effect to many organ systems and is responsible for illnesses such as lung cancer, pneumonia, chronic obstructive pulmonary disease, cancer of head and neck, cancer of the urinary and gastrointestinal tract, periodontal disease, cataract and arthritis. Additionally, smoking is an important modifiable risk factor for the development of cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(92 citation statements)
references
References 0 publications
1
90
0
1
Order By: Relevance
“…Similarly, some natural compounds also protect endothelial cells from ox-LDL-induced apoptosis by modulating the PI3K/Akt/eNOS pathway [44]. In contrast, many studies indicated that decreased NO is another key mechanism underlying endothelial dysfunction, which is interrelated with decreased expression of the Klotho gene [33, 4547]. In addition, it has been proven that Klotho protects the cardiovascular system through endothelium-derived NO production by humoral pathways [47].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some natural compounds also protect endothelial cells from ox-LDL-induced apoptosis by modulating the PI3K/Akt/eNOS pathway [44]. In contrast, many studies indicated that decreased NO is another key mechanism underlying endothelial dysfunction, which is interrelated with decreased expression of the Klotho gene [33, 4547]. In addition, it has been proven that Klotho protects the cardiovascular system through endothelium-derived NO production by humoral pathways [47].…”
Section: Discussionmentioning
confidence: 99%
“…Further, these diseases share chronic inflammation and oxidative stress as common hallmarks (Barua, Sharma, and Dileepan 2015;Crotty Alexander, Shin, and Hwang 2015;Kelly and Fussell 2015;Siasos et al 2014;Valavanidis et al 2013), suggesting some overlap in the biological processes underlying disease development. Extracellular vesicles (EV) are secreted signaling entities whose production is modulated by pro-inflammatory and oxidative stimuli in vitro.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…One manifestation of this is an increase in plasma concentration of natriuretic peptides, which have a significant diagnostic and prognostic meaning in CHF. The basic natriuretic peptide with a recognised role in diagnostics as well as in monitoring the treatment of CHF patients is plasma concentration of N-terminal pro-B-type natriuretic peptide (NT-proBNP) [37,[39][40][41][42][43][44][45][46].…”
Section: Cardiologists and Periodontistsmentioning
confidence: 99%